1999
DOI: 10.1136/hrt.82.6.674
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome after out-of-hospital cardiac arrest with physician staffed emergency medical services: the Utstein style applied to a midsized urban/suburban area

Abstract: Results-Of 330 000 inhabitants, 755 suffered from cardiac arrest covered by the Heidelberg ALS services. In 512 patients, cardiopulmonary resuscitation had been initiated. Of 338 patients with cardiac aetiology, return of spontaneous circulation was achieved in 164 patients (49%), 48 (14%) were discharged alive, and 40 (12%) were alive one year later; most of these patients showed good neurological outcome. Thus, 4.85 patients with cardiac aetiology were saved by the ALS services and discharged alive per 100 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
3
30

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(102 citation statements)
references
References 22 publications
2
67
3
30
Order By: Relevance
“…International data suggested that OHCA at residence were less likely to be witnessed and have poorer outcome, [10] likewise in our study too, OHCA at home was associated with poor survival outcome as compared to public place.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…International data suggested that OHCA at residence were less likely to be witnessed and have poorer outcome, [10] likewise in our study too, OHCA at home was associated with poor survival outcome as compared to public place.…”
Section: Discussionsupporting
confidence: 54%
“…OHCA was more common in males (70%) as compared to females ( =0.003). International studies [4,10] showed that 61.1% to 70.1% were males who experienced OHCA where as Indian study by Rajaram et al showed 66% males. These data do suggest that males are more prone for OHCA than females; but regarding relationship between survival after OHCA and sex of the individual, it was statistically non-signifi cant; further studies with large number of samples in this context are required.…”
Section: Discussionmentioning
confidence: 99%
“…However, fewer than 20% of patients with CA fulfill the inclusion criteria for these studies [171] .…”
Section: Indications For Ttmmentioning
confidence: 99%
“…4,5,15,[23][24][25][26][27] This low rescue rate might be partly explained by the long interval (approximately 5 min) from emergency call to the ambulance's arrival at the scene. Another plausible explanation is that the proportion of aged people with inherently poor recovery has greatly increased in Japan in recent years.…”
Section: Discussionmentioning
confidence: 99%